2005
DOI: 10.2117/psysoc.2005.288
|View full text |Cite
|
Sign up to set email alerts
|

The After-Effects of Regulating Anger and Anger-Related Emotions on Self-Report Ratings and Behavior: Divergent Consequences for Men and Women

Abstract: Despite the reported frequency of anger in everyday life, comparatively little is known about the psychological consequences of regulating this emotion. In the present study male and female participants were exposed to a short anger arousing film clip under one of three conditions: Expression (participants were asked to respond spontaneously to the events depicted in the film clip); suppression (participants were asked to inhibit outward expressions of emotion); and substitution (participants were asked to rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…It may also be that the present study did not assess certain facets of ER shown in past literature to capture sex differences. For instance, research has demonstrated that, in Western cultures, there are sex differences in how anger and sadness are regulated across age groups (e.g., Hosie, Milne, & McArthur, 2005; Thomsen, Mehlsen, Viidik, Sommerlund, & Zachariae, 2005; Zeman & Garber, 1996), but the present study did not assess ER difficulties by emotion type.…”
Section: Discussionmentioning
confidence: 73%
“…It may also be that the present study did not assess certain facets of ER shown in past literature to capture sex differences. For instance, research has demonstrated that, in Western cultures, there are sex differences in how anger and sadness are regulated across age groups (e.g., Hosie, Milne, & McArthur, 2005; Thomsen, Mehlsen, Viidik, Sommerlund, & Zachariae, 2005; Zeman & Garber, 1996), but the present study did not assess ER difficulties by emotion type.…”
Section: Discussionmentioning
confidence: 73%